Ileal Perforation from Intestinal Tuberculosis in Migrant Workers - Soimadee, Smith (Journal of Health Science of Thailand, 2018)
Intestinal perforation is an uncommon complication of intestinal tuberculosis mostly reported among HIV infected cases. This report presents a 36-year-old HIV negative foreigner labor man who developed terminal ileal perforation from tuberculous ileitis confirmed by pathological report. Chest X-rays showed no evidence of concomitant pulmonary lesions. Explore laparotomy showed matted mass formed by cecum, some part of terminal ileum and fibrosis caused distal small bowel obstruction. As such, right half colectomy with end to end ileotransverse colostomy was done. Anti-tuberculous medications in CAT 1 regimen were prescribed. The patient had an uneventful recovery postoperatively. History of drinking unpasterized cow milk was reported.